2016
DOI: 10.1007/s11356-016-6931-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of soil amendments as a remediation alternative for cadmium-contaminated soils under cacao plantations

Abstract: Elevated plant-available cadmium (Cd) in soils results in contamination to cacao (Theobroma cacao L) beans. Effectiveness of vermicompost and zeolite in reducing available Cd in three cacao-growing soils was studied under laboratory conditions. Sorption-desorption experiments were conducted in soils and amendments. Cadmium was added at 0 or 5 mg kg(-1) (spiked), then, amendments were incorporated at 0, 0.5, or 2 %. Amended soils were incubated at room temperature for 28 days. Plant-available Cd was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Of specific relevance is the decision of the EU regulatory authorities to reduce from 2019 the permissible levels of dietary Cd 2+ (Commission Regulation (EU) no 488/2014). In an attempt to reduce the levels of Cd 2+ in crops, including cacao (the source of chocolate), a variety of research studies are underway to develop agronomic 3 , 4 or genetic 5 solutions to this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Of specific relevance is the decision of the EU regulatory authorities to reduce from 2019 the permissible levels of dietary Cd 2+ (Commission Regulation (EU) no 488/2014). In an attempt to reduce the levels of Cd 2+ in crops, including cacao (the source of chocolate), a variety of research studies are underway to develop agronomic 3 , 4 or genetic 5 solutions to this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Respect to soil pH, our results differ from those reported by Liu et al (2015) who mentions that in order to reduce the Cd absorption by plants, the soil pH need to increase with the increase of OM in the soil. Chavez et al (2016) reported the soil pH increase up to 60 days after application of vermicompost and zeolite on cocoa plantation soil, but on day 75 the soil pH decreased. In our study, we registered a slight soil pH change after 9 months of applying the organic amendments (compost and poultry manure).…”
Section: Discussionmentioning
confidence: 97%
“…However, most cocoa farmers in Peru, generally do not fertilise their parcels with OA, unlike Andean farmers who use OA, mainly livestock manure as fertilizer. In that sense, the presence, absorption and accumulation of heavy metals by cocoa plants may be related to soil characteristics such as pH, soil organic matter (OM) content, soil cation exchange capacity (CEC), among others (Chavez et al, 2016;Huamaní-Yupanqui et al, 2012), and these characteristics can be modified by OA application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that pH and organic matter in soils are related to the absorption of Cd in cacao plants. 5,[48][49][50][51][52][53][54][55][56] Thus, several studies have used lime, 55,56 organic matter amendments 48 or biochar 20,24,[49][50][51]55 to manage Cd absorption by cacao plants. Lime acts mainly increasing soil pH, and it has been reported that the sorption of Cd in soils increases by a factor of 3 to 5 for each unit of increase in pH, 4 and organic matter causes Cd retention in soils by surface adsorption or by generating complexes with the Cd ions.…”
Section: Discussionmentioning
confidence: 99%